Role of doppler ultrasound in detecting vascular complications in recipients of living donor liver transplant (LDLT) - Hussain, Huma; Muhammad Salman Rafique,; Sana Kundi,; Tahir Malik,; Ahmad Zia Ud din,; Abdullah Saeed, (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the role of Doppler ultrasound in the detection of vascular complications in recipients of living donor liver transplant, keeping contrast-enhanced computerised tomography of abdomen as the gold standard. Method: The retrospective study was conducted from February 16 to April 1, 2022, at the Pakistan Kidney and Liver Institute and Research Centre, Lahore, Pakistan, and comprised data of living donor liver transplant recipients who had undergone contrast-enhanced computerised tomography of abdomen within 24 hours of Doppler ultrasound between January 2021 and January 2022. For the diagnosis of hepatic vascular complications, the diagnostic values of Doppler ultrasound parameters were derived by correlating Doppler ultrasound findings with contrast-enhanced computerised tomography results. Data was analysed using SPSS 20. Results: Of the 35 patients, 24(68.6%) were men and 11(31.4%) were women. The overall mean age was 45.86±13.8 years. For hepatic artery thrombosis, the use of Doppler ultrasound criteria yielded a sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of 100%, 96.6%, 83.3%, 100%, and 97.1% respectively. For hepatic artery stenosis, overall sensitivity, specificity, positive predictive value, negative predictive value and accuracy of Doppler ultrasound was 100%, 96.8%, 75%, 100% and 97.1% respectively. Doppler ultrasound parameters resulted in a sensitivity, specificity, positive predictive value, negative predictive value and accuracy of 100% each in detecting portal vein and hepatic venous outflow tract thrombosis. Overall, Doppler ultrasound sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy was found to be 100%, 88.8%, 89.4%, 100% and 94.2% respectively. Conclusion: Doppler ultrasound was adequate to document vascular complications after living donor liver transplant in majority of the cases with high accuracy and sensitivity. Key Words: CLD, Doppler US, Vascular complications, LDLT recipients, CECT abdomen.